Dwell-time conditions for exponential stability and standard L1-gain performance of discrete-time singular switched positive systems with time-varying delays. (November 2020) - Li, Shuo; Xiang, Zhengrong; Zhang, Junfeng
Abstract: This paper addresses the dwell-time issues on exponential stability and standard L 1 -gain performance of discrete-time singular switched positive systems with time-varying delays. The dwell-time constraints refer to mode-dependent minimum dwell time(MDMDT), mode-dependent constant dwell time(MDCDT) and mode-dependent ranged dwell time(MDRDT). At first, a sufficient delay-dependent condition of exponential stability for delayed singular switched positive systems under three different kinds of dwell time constraints: MDMDT, MDCDT and MDRDT, is provided, respectively. Then, considering the disturbance attenuation performance, a sufficient condition of standard L 1 -gain performance for delayed SSPSs with dwell-time constraints: MDMDT, MDCDT and MDRDT, is proposed, respectively. Meanwhile, the corresponding dwell-time results of exponential stability and standard L 1 -gain performance for the system in delay-free case is also presented. Four examples are finally presented to show the feasibility and effectiveness of the obtained results.